Acute HIV-1 Infection: Paradigm and Singularity - Antoine Chéret (Viruses)
Acute HIV-1 infection (AHI) is a transient period where the virus causes evident damage to the immune system, including an extensive apoptosis of CD4+ T cells associated with a high level of activation and a major cytokine storm to fight the invading virus. HIV infection establishes persistence by integrating the viral genome into host cell DNA in both replicating and non-replicating forms, effectively hiding from immune surveillance within infected lymphocytes as cellular reservoirs. The measurement of total HIV-1 DNA in peripheral blood mononuclear cells (PBMCs) is a reliable reflection of this reservoir. Initiating treatments during AHI with nucleoside reverse transcriptase inhibitors (NRTIs) and/or integrase strand transfer inhibitors (INSTIs) is essential to alter the dynamics of the global reservoir expansion, and to reduce the establishment of long-lived cellular and tissue reservoirs, while preserving and enhancing specific and non-specific immune responses. Furthermore, some of the patients treated at the AHI stage may become post-treatment controllers and should be informative regarding the mechanism of viral control, so patients treated during AHI are undoubtedly the best candidates to test innovative remission strategies toward a functional cure that could play a pivotal role in long-term HIV control. AHI is characterized by high levels of viral replication, with a significant increase in the risk of HIV transmission. Detecting AHI and initiating early treatment following diagnosis provides a window of opportunity to control the epidemic, particularly in high-risk populations.